The Influence of Perceived Quality, Value, Satisfaction, Trust, Commitment on Loyalty and Strategies to Increase Loyalty - Yuliati, Lilik Noor; Taryana, Asep; Anggraini, Zunika Dwi (Universitas Brawijaya, Indonesia, 2024)
The manufacturing sector, including the automotive industry, is vital to the Indonesian economy. The research was conducted at a company engaged in automotive components. In increasingly fierce competition, companies foster long-term relationships to win customers. This research aims to analyze the effect of relational marketing variables on loyalty using quantitative methods and then design strategies to increase customer loyalty using qualitative methods. The initial stage of the research is to identify the existing relationship marketing implementation, then analyze the influence using the PLS-SEM quantitative method involving 100 respondents, and then the analysis is used to formulate strategy priorities using the SWOT matrix qualitative method involving 3 respondents. The results showed that perceived quality has a significant effect on perceived value. Perceived quality has a significant effect on customer satisfaction. Perceived value has no significant effect on customer satisfaction. Customer satisfaction has a significant effect on trust. Perceived value has a significant effect on commitment. Trust has a significant effect on loyalty. Commitment has no significant effect on loyalty. Then, the managerial implications carried out as a result of strategic prioritization are improving product quality to reduce customer complaints, creating wider market opportunities, and increasing customer loyalty.